Matrix Calculator Based on Android as The Implementation of Independent Campus Learning: Kalkulator Matriks Berbasis Android Sebagai Pengejawantahan Merdeka Belajar Kampus Merdeka - Ariyanti, Novia; Taurusta, Cindy; Amir, Mohammad Faisal (Universitas Muhammadiyah Sidoarjo, 2022)
This encourages educators to be creative and innovate by optimizing the use of rapidly growing technology. One of them is mathematics which must able to innovate in making learning media. In previous studies, calculations on existing mobile or web calculators were only limited to matrix operations. The purpose of this research is to make a modification of calculating machine and add features to the matrix calculator to find a solution to a system of equations using the Cramer method. This type of research is research and development (R&D). The model used in this development is the ADDIE which includes five stages, namely Analyze, Design, Development, Implementation and Evaluation.